Identifikasi Kecerdasan Interpersonal Anak Usia 5-6 Tahun di TK Al-Muttaqin - Pratiwi, Oppy Anggun; Syafrudin, Ulwan; Oktaria, Renti (Universitas Islam Negeri Sumatera Utara, 2023)
The purpose of this study was to measure the development of interpersonal intelligence in children aged 5-6 years at Al Muttaqin Kindergarten, Baradatu District, Way Kanan Regency. This research is motivated by the existence of children's behavior that has not led to the interpersonal intelligence of children at the age of 5-6 years. This research is a type of research with a quantitative descriptive approach. The subjects of this study were 22 children in Group B of Al-Muttaqin Kindergarten, Baradatu District, Way Kanan Regency. The object of this research is interpersonal intelligence. Data collection techniques used are observation and documentation. The research instrument was in the form of an observation sheet (checklist). The results of this study are that the interpersonal intelligence of children aged 5-6 years in Al-Muttaqin Kindergarten, Baradatu District, Way Kanan Regency is included in the good criteria. The development of children's interpersonal intelligence can be influenced by several factors, including the stimulation given to children, differences in individual characteristics, and the environment that influences differences in individual behavior.